Tinjauan literatur sistematis tentang tren penelitian penyebaran hoax selama pandemi COVID-19 di Indonesia - Nur Sanny Rahmawati; Tamara Adriani Salim (Perpustakaan Universitas Gadjah Mada, 2021)
Introduction. Awareness about the spread of hoaxes through the media during the COVID-19 pandemic in Indonesia should be the main concern for everybody. Data Collection Methods. This paper used a systematic literature review method with a qualitative approach, using the literature which focuses on the spread of hoaxes through the media during the COVID-19 pandemic from Google Scholar, Garuda RistekBRIN, and Research Gate. The exclusion process resulted in 20 scientific papers for further analysis. Data Analysis. Data analysis was conducted manual using graphs and tables to systematize the most relevant information to the research topic. Results and Discussion. Three research questions were answered, including the quantity of publications regarding the spread of hoaxes through media during the pandemic in Indonesia, the focus of the researches, and the methodology used in the study. Based on the findings, 20 scientific papers were obtained, with minor topics including the identification of hoax news about COVID-19 on social media, information behavior on social media during the COVID-19 pandemic, and strategies dealing with the spread of hoaxes during the pandemic. Conclusion. There are many papers discussing the spread of hoaxes through the media during the COVID-19 pandemic in Indonesia and this needs sufficient attention.